Estudio de prefactibilidad para la instalación de una empresa de monitoreos ergonómicos, psicosociales y de agentes físicos para el trabajo remoto - Barco Palomino, Jorge Jesus (2024)
The monitoring service item represents a sector with continuous growth since more and more companies are focusing on the care of employees to improve productivity, work environment and therefore reduce costs. Therefore, there is a close relationship between working conditions and labor efficiency, according to what is stated in the following pages. The COVID-19 pandemic represents an opportunity in this regard, since many companies continue to opt for remote work, so the self-managed tools to be used make them useful at any level of the organization. The present pre-feasibility work evaluates the technical, economic and social pre-feasibility for the installation of an office that offers services related to occupational safety, which are ergonomic monitoring, physical and psychosocial agents, for which the target market will be studied and Establish with a good analysis of the demand, the place of the work office and subsequent marketing strategies that increase the income of the project will be established. Studying the potential demand, more than 26,000 people in Lima would be served, given that the concern and importance regarding the labor ergonomics issue has been very recurrent and important in labor efficiency in recent years, serving approximately three clients or companies (approximately 500 workers) every week of the year. With a working capital of 168 thousand soles, the recovery period is expected to be 3 years and 7 months in the financial evaluation. Given this and adding added values of the ergonomic theme such as active breaks, talks or communicative digital flyers, it can be concluded that we will have loyalty from a large part of customers who would renew for the services offered by adopting merchandising strategies; given that the increase in productivity in employees would be reflected, as well as the reduction of work stress and disergonomic diseases arising from the lack of knowledge of forced postures and the misuse of furniture. From this, the project on the monitoring service would follow a path of projected feasibility.